PENGARUH MOTIVASI, KEPUASAN KERJA, DAN STRES KERJA TERHADAP KINERJA KARYAWAN PT TOYOTA AGUNG AUTOMALL BENGKULU - Rendy Alpahrasy; Nasution Nasution (Unib Press Universitas Bengkulu, 2017)
The purpose of this study is know that a influence of motivation, job satisfaction, and work stress on employee’s performance of PT. Toyota Agung Automall Bengkulu. The subject of this study are employee who have worked on PT Toyota Agung Automall Bengkulu. Data were collected via questionnaires. 175 effective samples were collected to verify the hypotheses of this study. For data analysis and hypotheses testing, multiple linier regresion techinque was used. Sampling techinique in this study using census method. The result show that a motivation and job satisfaction have a positive and significant effect on employee performance, and work stress is significantly effect on employee performance. Keywords: motivation, stress, performance